2021
DOI: 10.1097/iop.0000000000001940
|View full text |Cite
|
Sign up to set email alerts
|

Kelly Punch Punctoplasty and Simple Punctal Dilatation Are Equally Effective for Punctal Stenosis: A Prospective Study

Abstract: Purpose: To examine the clinical, imaging, and histopathologic differences between Kelly punch punctoplasty and punctal dilatation, both with mini Monoka stent insertion. Methods: This is a prospective, comparative clinical study. Patients with bilateral punctal stenosis and for whom surgery was advised participated in the study. The right eye underwent Kelly punch punctoplasty and the left eye simple punctal dilatation, both with mini Monoka stents wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In this study, it was discovered that using AS-OCT characteristics was an effective way to track and gauge how well medical care was working to relieve punctal blockage. AS-OCT has been employed in earlier investigations to characterize puncta in both healthy individuals and patients with punctal stenosis [11]. The study found that the outer punctal diameter (OPD) measured by AS-OCT was significantly improved in groups I and III after treatment compared to before, with the greatest improvement rate in group III.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, it was discovered that using AS-OCT characteristics was an effective way to track and gauge how well medical care was working to relieve punctal blockage. AS-OCT has been employed in earlier investigations to characterize puncta in both healthy individuals and patients with punctal stenosis [11]. The study found that the outer punctal diameter (OPD) measured by AS-OCT was significantly improved in groups I and III after treatment compared to before, with the greatest improvement rate in group III.…”
Section: Discussionmentioning
confidence: 97%